Development of Battery Pack for Electric Motorcycle Complying with Safety Standard and Indonesia Regulation - Widyantara, Robby Dwianto; Wicaksono, Dito Ata'ul Momin; Priyatama, Syafiq Ade; Nugroho, Andika Pandu; Wiradibrata, Raihan; Agustin, Anggi Regiana; Tianqi, Lei; Wibowo, Agung; Nurprasetio, Ignatius Pulung; Budiman, Bentang Arief (Automotive Experiences, 2025)
This paper presents a comprehensive design methodology and mechanical evaluation of an electric motorcycle battery pack that fulfils both international safety standards and Indonesian regulations. As the country with the world’s largest motorcycle fleet, Indonesia faces significant challenges in transitioning to electric mobility—particularly in preventing battery malfunctions and mitigating accident risks. The design process begins by defining minimum technical requirements, ensuring regulatory compliance, and addressing geometric constraints, then moves on to develop component architectures in accordance with industry best practices. Detailed models of the pack and its subassemblies are subjected to finite element analysis to verify structural integrity under demanding operational conditions. Key performance targets include an IP68 ingress protection rating, sufficient rigidity to withstand vibrational loads, and impact resistance for accident scenarios. Simulation results confirm that the final design maintains mechanical robustness across a variety of load cases. Building on these findings, the paper offers specific recommendations to further enhance pack performance and safety. The described methodology is fully reproducible and provides practical insights for efficient product development, even when resources are limited.